ANALISIS STABILITAS LERENG BOJA – DARUPONO STA. 10+720 JAWA TENGAH DAN USULAN PENANGANANNYA - Indra Adrianto; Indah Duanita Pusparini; Sri Prabandiyani; Bambang Pardoyo (Jurnal Karya Teknik Sipil, 2016)
The landslide occurred on road Boja – Darupono Sta. 10+720 created a long traffic jam and holding up economic development between Kendal and Semarang. By analyzing the slope stability by using Fellenius method, it is shown that the SF or safety factor of the slope is 1,19 for the radius of the circle ( R ) = 28,67 and 1,63 for R = 27,09. While SF on a Plaxis V.8.2 program is 1,19, so it can be concluded that the slope in critical condition because of the SF on Plaxis V.8.2 program smaller than that of 1,5 safe although the safety factor on Fellenius value is greater than the value of safe SF. The first alternative of slope reinforcement is a Bored pile, the second alternative is Geotextille with a Counter weight. Based on finite element method calculation using Plaxis V.8.2 program, reinforcement with Bored pile produce SF = 1,75 and Geotextille with a Counter weight SF = 1,5. This form these two alternatives, Bored pile reinforcement has the greatest, so can be considered as the best alternative solution.